1992
DOI: 10.1109/20.179493
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the archival life of metal particulate tape

Abstract: Abslruct -The oxidization stability o f metal particulate tape has b e e n studied u s i n g h i g h temperature a n d humidity a s a c c e l e r a t i n g parameters. By fitting the obtained oxidation rate t o the Arrhenius scale, the tape's archival life determined by oxidation has been estimated.The results sug est that the current metal tape has more than $0 years of archivul life and that of the improved tape i s four times longer. T h i s improvement was achieved by developing a new metal particle which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Tape-based storage solutions, such as CERN's CTA service, provide a reliable and cost-effective means of preserving large quantities of data over extended periods of time. Tapes have been proven to be resilient to data corruption and physical damage [9][10][11], positioning them as the preferred choice for disaster recovery scenarios and long-term archival. Furthermore, tapes cost significantly less per terabyte compared to traditional hard disk solutions.…”
Section: Tape Advantagesmentioning
confidence: 99%
“…Tape-based storage solutions, such as CERN's CTA service, provide a reliable and cost-effective means of preserving large quantities of data over extended periods of time. Tapes have been proven to be resilient to data corruption and physical damage [9][10][11], positioning them as the preferred choice for disaster recovery scenarios and long-term archival. Furthermore, tapes cost significantly less per terabyte compared to traditional hard disk solutions.…”
Section: Tape Advantagesmentioning
confidence: 99%
“…Many studies have been carried out to determine the environmental stability of tapes to evaluate lifetime expectancy [55,56] It was shown that long-term stability of magnetic tape is dependent upon many factors including integrity of polymer binder and oxidation of the metal particles. It is worth noting that the chemical age of a tape cannot be understood exclusively on the basis of the calendar time, but depends on the conditions of storage.…”
Section: Tape Degradation Problemsmentioning
confidence: 99%
“…Another study [3] reported remanent magnetization measurements on M P tape exposed to 90% relative humidity and either 35"C, 50"C, or 65°C. These authors estimated the archival lifetime of MP tape to exceed 20 years.…”
Section: Introductionmentioning
confidence: 99%